2018
DOI: 10.5194/amt-11-6703-2018
|View full text |Cite
|
Sign up to set email alerts
|

Lidar temperature series in the middle atmosphere as a reference data set – Part 2: Assessment of temperature observations from MLS/Aura and SABER/TIMED satellites

Abstract: Abstract. We have compared 2433 nights of Rayleigh lidar temperatures measured at L'Observatoire de Haute Provence (OHP) with co-located temperature measurements from the Microwave Limb Sounder (MLS) and the Sounding of the Atmosphere by Broadband Emission Radiometry instrument (SABER). The comparisons were conducted using data from January 2002 to March 2018 in the geographic region around the observatory (43.93∘ N, 5.71∘ E). We have found systematic differences between the temperatures measured from the grou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 27 publications
4
28
0
Order By: Relevance
“…The dispersion of the differences remains relatively constant with altitude and has an approximate value of ±5 K over the entire altitude range. The positive relative bias in the upper part of the profile may be at least partially due to a warm bias in OHP temperature above 75 km as reported by Wing et al (2018b) using a comparison with SABER-TIMED. Below 75 km, the alternation between positive and negative relative biases with altitude may indicate a contribution of the atmospheric thermal tides, as the temperature measurements are not obtained simultaneously.…”
Section: Validation Using Rayleigh Lidar Observationsmentioning
confidence: 53%
See 2 more Smart Citations
“…The dispersion of the differences remains relatively constant with altitude and has an approximate value of ±5 K over the entire altitude range. The positive relative bias in the upper part of the profile may be at least partially due to a warm bias in OHP temperature above 75 km as reported by Wing et al (2018b) using a comparison with SABER-TIMED. Below 75 km, the alternation between positive and negative relative biases with altitude may indicate a contribution of the atmospheric thermal tides, as the temperature measurements are not obtained simultaneously.…”
Section: Validation Using Rayleigh Lidar Observationsmentioning
confidence: 53%
“…Further work would be needed to confirm this hypothesis. The comparison of OHP lidar temperature profiles with MLS-Aura and SABER-TIMED indicated systematic differences and suggested non-linear distortions in the satellite altitude retrievals (Wing et al, 2018b). In order to better understand these differences, we plan to compare our new GOMOS temperature data set with MLS and SABER in a future work.…”
Section: Validation Using Rayleigh Lidar Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more thorough comparison made by Schwartz et al (2008) compared EOS MLS temperature retrievals to those from radiosondes, several satellites, and from GPSRO. It was found that from 0.0001 hPa to 0.3 hPa that temperature bias could range from -9 to 0K with temperature precision ranging from ±1 to ±2.5 K. A further study by Wing et al (2018a) found that the bias in wintertime MLS was ±10 K and ±4 K in the summertime. At 1 hPa warm biases from 0 to 5K were found.…”
Section: Microwave Limb Soundermentioning
confidence: 93%
“…While all the lidars were measuring at the same location and the same time during LAVANDE, and the ECC sondes were quite close in time and space, satellite profiles almost never match the exact time and location of a ground-based measurement. For LAVANDE, we considered all satellite profiles with a tangent point within ±5 • latitude and ±15 • longitude of the OHP station (43.94 • N, 5.71 • E), and within ±12 hours of 00 UTC (1 hour after local midnight for the lidar measurements nights) (see also Wing et al, 2018b). This fairly large coincidence box is depicted in Fig.…”
Section: Co-locating Satellite Profiles and Ground-based Profilesmentioning
confidence: 99%